An Analysis on Communication Strategy Used by Front Office Staff In Puri Saron Baruna Hotel - ., Luh Putu Widianingsih; ., Drs. Asril Marjohan,MA; ., I G A Lokita P Utami, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk mengetahui strategi berkomunikasi yang digunakan oleh staf front office, tipe dari strategi berkomunikasi yang paling sering digunakan oleh staf ketika berkomunikasi dengan tamu, dan alasan dalam penggunaan strategi tersebut. Data dikumpulkan melakui observasi langsung dan wawancara. Alat perekam, catatan, dan lembar pengamatan juga digunakan dalam pengumpulan data. Data tersebut kemudian dianalisis secara kuantitatif dan kualitatif. Hasil dari penelitian ini yaitu; (1) Tipe-tipe dari strategi berkomunikasi yang digunakan oleh staf front office adalah message abandonment, topic avoidance, language switch, approximation, word coinage, circumlocution, appeals for assistance, stealing atau time-gaining strategies, non linguistic signals, dan literal translation. (2) Strategi stealing atau time gaining merupakan strategi yang digunakan paling sering oleh staf. (3) Ada beberapa alasan yang menyebabkan para staf menggunakan strategi tersebut seperti untuk memperlancar komunikasi dengan tamu walaupun staf memiliki keterbatasan dalam penguasaan bahasa tertentu, untuk memberikan penekanan terhadap ujaran dari staf, untuk membantu staf dalam menjelaskan sesuatu kepada tamu, dan menghindari kesalahan dalam memberikan informasi.Kata Kunci : staf front office, strategi berkomunikasi The purposes of this study were to investigate the types of communication strategy used by front office staff, the types of communication strategy used most frequently, and the reasons of the staff in using those types of communication strategies. The data was collected through doing direct observation and interview. Besides, mobile recorder, field note, and observational sheet were also used in gaining the data. The data was analysed both qualitatively and quantitatively. The result of this study are: (1) there are ten types of communication strategies utilized by the staff in communicating with the guests, they are message abandonment, topic avoidance, language switch, approximation, word coinage, circumlocution, appeals for assistance, stealing or time-gaining strategies, non linguistic signals, and literal translation. (2) Stealing or time gaining strategy is found as the most frequent strategy used by the staff. (3) There are some factors that cause the staff to apply those strategies such as to make the conversation keep running although the staff have lack of language ability, to give emphasize on staffâs utterances so that the guest understand what the staff said, to help the staff explain something easier to the guests, and to avoid mistakes while giving information to the guests. keyword : communication strategy, front office staff